The Phonology Course E-Module Using the Canva Application - Simaremare, Juni Agus; Beslina Afriani Siagian; Renita Saragih (Journal of Education Technology, 2025)
Students' lack of mastery of phonology courses is the basis for conducting this research. The factor causing the low ability of students is the minimal availability of teaching materials. The research objectives are 1) To produce a phonology e-module based on the Canva application; 2) find out the feasibility of e-modules based on the Canva application; 3) find out student responses to the development of e-modules based on the Canva application. This type of research is development research. The development model for this research uses a 4-D model (four D Model). The findings of this research are that e-modules are suitable for use as teaching materials for students. This feasibility is proven by the percentage of material expert validation obtained at 97.72% for the appropriateness aspect of content, 89.28% for the appropriateness aspect of presentation, 90% for the appropriateness aspect of language. Based on these three aspects, the feasibility of the material is 92.33% in the very feasible category. Then the media expert validation obtained a percentage of 88.22% with a very feasible category. The results of individual trials on this e-module are in the very good category with a percentage of 95%. In the small group trial, it was in the very good category with an average of 92.25%. Meanwhile, in the large group trial, the percentage obtained was 83.23% in the very feasible category. Based on this percentage, it can be concluded that this e-module is suitable for use as teaching material for phonology courses.